A case study on Sema3E-Fc aggregation and assay-dependent differences in quantitation. (March 2012) - Bumbaca, Daniela; Tong, Raymond K; Koch, Alexander W; Xiang, Hong; DeForge, Laura E; Shen, Ben-Quan; Lu, Yanmei
Background: In evaluating the serum concentrations in mice of a Sema3E IgG1 Fc fusion protein, a possible antitumor agent, two ELISAs were developed: a generic assay detecting only the Fc portion of the therapeutic and a specific receptor-binding assay detecting intact protein.Results: An unexpected discrepancy was observed in the measured in vivo serum concentrations, with the generic ELISA yielding higher concentrations than the specific ELISA. Size-exclusion HPLC and SDS-PAGE analysis of in vitro serum stability samples revealed extensive aggregation of Sema3E-Fc. The generic assay recovered more Sema3E-Fc in the presence of aggregates than the specific assay.Conclusion: Biophysical characterization combined with immunochemical analysis was key to elucidating not only the nature of the protein instability, but also the cause for the assay discrepancy.